2020
DOI: 10.1021/acsami.0c05106
|View full text |Cite
|
Sign up to set email alerts
|

On the Nature of Charge-Injecting Contacts in Organic Field-Effect Transistors

Abstract: Organic field-effect transistors (OFETs) are key enabling devices for plastic electronics technology, which has a potentially disruptive impact on a variety of application fields, such as 2 health, safety and communication. Despite the tremendous advancements in understanding the OFET working mechanisms and device performance, further insight into the complex correlation between the nature of the charge injecting contacts and the electrical characteristics of devices is still necessary. Here, an in-depth study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 70 publications
2
17
0
Order By: Relevance
“…Currently, in organic electronics, metal layers are usually deposited on organic films via thermal evaporation to form electrodes, while metal deposition process inevitably leads to disorders of organic surface and even damages the chemical structures. [22][23][24] It is generally believed that, besides the energy level mismatch produced injection barrier, the disorders and damages increase the contact resistance, which is disturbing for obtaining an ideal metal/organic contact interface. [22][23][24][25] Several methods have been proposed to reduce the contact resistance and improve charge injection at metal/organic interface, such as contact doping, introducing a charge injection layer, or forming an abrupt damage-free metal/semiconductor interface by transferred electrodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, in organic electronics, metal layers are usually deposited on organic films via thermal evaporation to form electrodes, while metal deposition process inevitably leads to disorders of organic surface and even damages the chemical structures. [22][23][24] It is generally believed that, besides the energy level mismatch produced injection barrier, the disorders and damages increase the contact resistance, which is disturbing for obtaining an ideal metal/organic contact interface. [22][23][24][25] Several methods have been proposed to reduce the contact resistance and improve charge injection at metal/organic interface, such as contact doping, introducing a charge injection layer, or forming an abrupt damage-free metal/semiconductor interface by transferred electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] It is generally believed that, besides the energy level mismatch produced injection barrier, the disorders and damages increase the contact resistance, which is disturbing for obtaining an ideal metal/organic contact interface. [22][23][24][25] Several methods have been proposed to reduce the contact resistance and improve charge injection at metal/organic interface, such as contact doping, introducing a charge injection layer, or forming an abrupt damage-free metal/semiconductor interface by transferred electrodes. [2,5,[24][25][26][27][28][29][30] However, these methods require additional and complicated processes, which increase the difficulty of device fabrication and some of them also…”
Section: Introductionmentioning
confidence: 99%
“…From the viewpoint of composite atoms, a high proportion of highperformance semiconducting polymers contain S atoms in their backbones. Upon utilizing Au as the electrode material, these S atoms could facilitate Au−S binding 19 through physical/chemical absorption and may contribute to charge injection. Compared to their p-type counterparts, the n-type or ambipolar semiconducting polymers generally have inferior carrier mobility and stability.…”
Section: Backbone Design Of High-performance Semiconducting Polymersmentioning
confidence: 99%
“…In this context, the same NT4N-based device was recently used to provide further insight into the complex correlation between the nature of the charge-injecting contacts and the electrical characteristics of devices. 89 The authors showed how the presence of thienyl sulfur atoms in NT4N determined the formation of chemical interactions with gold electrodes, with the consequent formation of small gold nanoclusters during the first stages of contact formation. Multiple analyses repeated at different stages of device fabrication, including also synchrotron X-ray spectroscopy on devices in operando, showed that the electrical performance was the result of the interplay between (i) the chemical composition of metal electrodes and the OSC, (ii) the type of physicochemical interactions at the metal/OSC interface, (iii) the interfacial morphology and (iv) the organization of the metal clusters at the OSC interface.…”
Section: Perspectivementioning
confidence: 99%